Milrinone Attenuates Heart and Lung Remote Injury after Abdominal Aortic Cross-Clamping - ALTURFAN, EBRU IŞIK; AK, ESİN (ELSEVIER SCIENCE INC, 2020)
Background: Phosphodiesterase enzymes play a pivotal role in the pathogenesis of ischemia/reperfusion (IR). We examined the role of milrinone (MIL), a phosphodiesterase 3 inhibitor, on remote injury of the heart and lung after abdominal aortic cross-clamping. Design: Experimental study. Methods: Twenty-one Wistar rats were divided into 3 groups: (1) control (C, n = 7), underwent laparotomy and exploration of abdominal aorta only; (2) IR (n = 7), normal saline was applied intraperitoneally (i.p) before IR induced by clamping of the abdominal aorta for 1 hr and then allowing reperfusion for 1 hr; and (3) MIL + IR (n = 7), MIL was given (0.5 mg/kg, i.p) before IR. After sacrification, the lungs and hearts were taken out for analyses and the tissue malondialdehyde (MDA) and glutathione (GSH) were studied. All tissues were examined under light microscopy and transmission electron microscopy (TEM). Expressions of caveolin (Cav)-1 in the lung and Cav-1 and Cav-3 in the heart were examined immunohistochemically. Results: The MIL + IR group had significantly a lower magnitude of oxidative stress than the IR group both in the lung and heart (lung: P = 0.03 for MDA and 0.001 for GSH and heart: P = 0.002 for MDA and 0.000 for GSH). In light microscopy, the MIL + IR group had statistically a lower total injury score than the IR group for both the lung and heart tissue (P = 0.03 and P = 0.04, respectively). In TEM, regression of mitochondrial degeneration and lamellar bodies in type II pneumocytes in the lungs and obvious improvements in disruption at the intercalated discs and mitochondrial degeneration in the hearts in the MIL + IR group were detected compared with the IR group. The expression of both Cav-1 and Cav-3 in the MIL + IR group was improved compared with the IR group (P = 0.03 for both). Conclusions: MIL attenuates remote injury of heart and lung in lower body IR by inhibiting oxidative stress. Moreover, Cav-1 and Cav-3 might have a potential role in MIL-induced cardioprotection.
Keywords: ISCHEMIA-REPERFUSION INJURY; ORGAN INJURY; EXPRESSION; CAVEOLIN-1; CYTOKINES; BLOCKADE